Aesthetic Habits in Performing Arts - Alessandro Bertinetto (Philosophies)
This article explores the connection between habits and the performing arts, arguing that habits are not only fundamental to the practice and appreciation of these arts but also inherently performative in nature. Drawing on insights from various philosophical traditions (including cognitive science, pragmatism, and phenomenology), it examines how habits function within artistic processes as resources for creativity and adaptation. Engaging critically with Noë’s interpretation of the entanglement between art and life, this article highlights the dual nature of habits: as routine practices that scaffold artistic expression and as dynamic, transformative elements responsive to specific cultural and performative contexts. By focusing on key notions such as gesture, style, and rituality in the performing arts, this article discusses the role of habits in aesthetic experiences, highlighting how habits shape both artistic performances and audience engagement. This perspective challenges traditional views that oppose habits to creativity, defending instead the idea that habits are creatively operative in both the performing arts and their reception.